Retinal safety evaluation of two-photon laser scanning in rats - Jayabalan, Gopal Swamy; Bille, Josef F.; Mao, Xiao Wen; Gimbel, Howard V.; Rauser, Michael E.; Wenz, Frederik; Fan, Joseph T. (Biomedical optics express, 2019)
Safe use of retinal imaging with two-photon excitation in human eyes is crucial, as the effects of ultrashort pulsed lasers on the retina are relatively unknown. At the time of the study, the laser safety standards were inadequate due to the lack of biological data. This article addresses the feasibility of two-photon retinal imaging with respect to laser safety. In this study, rat retinas were evaluated at various laser exposure levels and with different laser parameters to determine the effects of laser-induced optical damage. The results were experimentally verified using confocal reflectance imaging, two-photon fluorescein angiography, immunohistochemistry, and correlated to the IEC 60825-1 laser safety standard.
Gesehen am 05.08.2019